Teachers’ Perspective on Using Oral Peer Feedback in Public Speaking - Novita Sari Hidayat; Oikurema Purwanti; Slamet Setiawan (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Assessment activities are closely related to the process of learning activities that cannot be separated. There are three processes in teaching and learning activities. That is input, process and output. Peer assessment has an important role in an English learning process, especially in the realm of speaking. Input is the student himself, the process is related to the curriculum, teaching materials, and teaching methods. And output is the result of learning. Assessment is available in all three domains. Assessment is carried out before the learning process, when learning is carried out, and after learning is carried out. Because of the importance of assessment factors in learning, there are many forms of assessment during learning. One form of assessment that supports the process of learning English in the realm of speaking is peer assessment activities. Some researchers believe that peer assessment plays an active and beneficial role for both students and teachers themselves. This qualitative research aims to determine and evaluate the benefits of peer assessment and perceptions of four subject teachers in an upper secondary school as teaching material from the results of assessments conducted by their students. Data was obtained through semi-structured interviews containing opinions, challenges and benefits from the application they obtained from this oral peer feedback assessment method